The influence of enterprise architecture maturity on business value: a perspective from the South African financial services environment - Bachoo, Avsharn (My University, 2018)
Enterprise Architecture (EA) is viewed as a source of business value and competitiveness due to beneficial outcomes such as reduced system complexity, business-information technology (IT) alignment, and improved system integration. However, challenges exist in understanding the relationship between EA and business value at different maturity levels. This research focused on the connection between the EA maturity of an organisation and the business value associated with it in the South African (SA) financial services environment. This study analysed dominant EA frameworks, maturity models, as well as various explanations of the term business value from literature. The resource-based view of the firm (RBV) was used as the underlying theoretical framework to structure this research, by examining EA as an intangible resource, and maturity as a source of heterogeneity. This study further contributed to the RBV operationalisation debate, by using the Architecture Capability Maturity Model (ACMM) as a supporting theory to operationalise EA from a qualitative perspective. The critical realism philosophy, which states that mechanisms generate events, shaped this research by creating focus on the underlying EA mechanisms that led to business value, as well as insights into the opportunities and challenges organisations experience as they progress to higher levels of maturity. This study built a middle range theory using a qualitative approach. Moreover, characteristics of descriptive, exploratory, and explanatory research were used within this investigation. A case study strategy, comprising of semi structured interviews and artefacts was employed to collect data for this study. The results were subsequently examined using thematic analysis techniques. This study established that within level 1 maturity, minimal EA practices driven by a few staff members were in place. Forms of value such as hardware cost savings, software cost savings, and visualisation were experienced. Most of the business units fell within level 2 maturity, indicating that EA practices were still under development. Forms of value such as increased revenue, improved development time and reduced complexity were attained. Business units within level 3 had simple EA practices in place with clear target states. Process improvements, improved risk management and improved customer service were experienced. Within level 4 maturity, EA was fully integrated into the culture, with EA metrics defined. In addition, forms of value such as improved decision-making, innovation and enhanced customer insights were also experienced. None of the business units were rated within level 5 maturity. This study found that EA was generally implemented at a coarse granularity of refinement across levels 1 and 2 maturities, at a medium granularity within level 3, and a fine granularity within level 4 maturity. Further, this study demonstrated that EA is a source of both tangible and intangible forms of value.
Faculty of Commerce Department of Information Systems University of Witwatersrand Doctor of Philosophy Information Systems, 2018
Keywords: Management information systems; Strategic planning